Off-Target Effects of Clozapine-N-Oxide on the Chemosensory Reflex Are Masked by High Stress Levels - Martinez, Vena K.; Saldana-Morales, Fatima; Sun, Jenny J.; Zhu, Ping Jun; Costa-Mattioli, Mauro; Ray, Russell S. (Frontiers in Physiology, 2019)
Respiratory chemosensory circuits are implicated in several physiological and behavioral disorders ranging from sudden infant death syndrome to panic disorder. Thus, a comprehensive map of the chemosensory network would be of significant value. To delineate chemosensory neuronal populations, we have utilized pharmacogenetic Designer Receptors Exclusively Activated by Designer Drugs (DREADD) perturbations for acute neuronal perturbations in respiratory circuit mapping. Recent studies show that the biologically inert DREADD ligand clozapine-N-oxide (CNO) is back-metabolized into the bioactive compound clozapine in rodents, emphasizing the need for CNO-only DREADD-free controls, which have been carried out in several studies. However, we show that high CNO doses used in several chemosensory circuit mapping studies nonetheless affect the chemosensory ventilatory reflexes in control mice, which is unmasked by extensive habituation. Here, unhabituated control animals showed no differences in respiratory parameters after CNO administration, whereas habituated animals receiving the commonly used dose of 10 mg/kg of CNO show a deficit in the hypercapnic (high CO2) chemosensory reflex, which is not present in 1 mg/kg CNO treated or saline control groups. Our findings indicate that even in appropriately controlled studies, additional masked CNO off-target effects may exist and underscore the importance of using minimal doses of activating ligand in combination with high levels of habituation.